Supervision of the Village Consultative Body (BPD) in the Implementation of Infrastructure Development in Ilangata Village, Anggrek District, North Gorontalo Regency - Salma Hulinggi; Lisda Van Gobel; Tety Thalib (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the Supervision of the Village Consultative Body (BPD) in the Implementation of Infrastructure in Ilangata Village, Anggrek District, North Gorontalo Regency. This research consists of three focuses, namely Preliminary Supervision (Preliminary), Infrastructure Development Monitoring and Feedback Monitoring. The research method used is descriptive qualitative. The results of the study concluded that the initial structural supervision had not gone well. The supervisory pattern of the BPD with the village head tends to be one-way. Supervision of Infrastructure Development is not yet complete. Oversight of BPD and TPK feedback did not run optimally, so the existing development was not completed. It is suggested that it is necessary to change the initial supervision with a two-way supervision pattern, improve relations with more friendly organizational partners, and coordinate the development of all activities and use good direction.